Consumers' Knowledge, Attitudes, and Practices Toward Medicine Price Transparency at Private Healthcare Setting in Malaysia - Ahmad, Nur Sufiza; Hatah, Ernieda; Jalil, Mohamad Ridha; Makmor-Bakry, Mohd (Frontiers in Public Health, 2021)
Background: Price transparency for consumers includes the practice of making prices available for consumers to identify, compare, and choose the medicine that offers the desired level of value. This study aims to evaluate the knowledge, attitudes, and practices and factors that may influence the consumer good practice in medicine price transparency initiative in Malaysia’s private health care settings. Methods: A cross-sectional, self-administered survey was conducted between May and July 2019 among consumers attending the private healthcare institutions in Malaysia. The self-developed and validated survey consisted of four sections of the respondent’s demographic, 28-items with a mixture of closed-ended and graded Likert-scale answer options on knowledge, attitudes, and practices towards medicine price transparency initiative. Factors influencing good consumer practice towards medicine price transparency were modeled using Binary Logistic Regression. Results: A total of 679 respondents were included in the study. The mean age of respondents was 38 ±13.3 with the majority (n=420, 61.9%) were female. The respondents’ mean score of knowledge and attitudes on price transparency initiative was 5.6 ± 1.5 of the total score of 8 and 31.9 ± 4.0 of the total score of 40, respectively. Respondents had the lowest score over the practice of price transparency initiative with a mean score of 31.5 ± 5.6 of the total score of 60. Male, Chinese ethnicity, a high score on knowledge and attitudes, and high cost spent on medicines had influence respondents’ good practice of medicine price transparency initiative. Conclusion: Respondents’ practices on medicine price transparency initiatives were still low. Several strategies such as physical medicine price display and compulsory itemized billing need to be implemented to increase consumers’ empowerment for price transparency initiative in Malaysia.